Analysis of RBC Antibody Screening in a Hospital Population Over a Two Years Period (Global Journal of Medical Research, 2018)
RBC antibody screening plays an essential role in the pre-transfusion testing of the blood or blood products before blood transfusion in the recipients as well as in antenatal screening to prevent Rh-incompatibility. The antibody screening tests performed in a clinical laboratory / blood bank are designed to detect the presence of these unexpected antibodies especially all antibodies in the serum. Methods routinely used for detection of these antibodies are the Coomb's test (antihuman globulin test), both direct and indirect types.